The hidden impact of alcohol on young victims: an analysis of alcohol-related police offences resulting in hospitalisation - Scott Anthony Sims; Gavin Pereira; Daniel Fatovich; David Preen; Melissa O'Donnell (BMC, 2024)
Abstract Background Alcohol-related harm (ARH) is a significant public health concern affecting young individuals, particularly those involved in alcohol-related police incidents resulting in hospitalisation. However, the impact of alcohol on young victims remains under researched. This study aimed to identify the characteristics of offenders and victims involved in these incidents, analyse the types of offences, and understand the under-ascertainment of ARH in hospital records. Methods A retrospective longitudinal study of 12-24-year-olds born between 1980 and 2005 was conducted using linked data from hospital admissions, emergency department presentations, and police incident records. Alcohol-related incidents were identified based on the attending officers' opinions in the Western Australia Police's Incident Management System (IMS). Logistic and log-binomial regression were utilised to analyse the factors associated with victimisation and under-ascertainment of ARH. Results Our study included 22,747 individuals (11,433 victims and 11,314 offenders) involved in alcohol-related police incidents, with a small majority of victims being female (53%, n = 6,074) and a large majority of offenders being male (84.3%, n = 9,532). Most victims did not receive a diagnosis of ARH (71%, n = 760). Women were 10 times more likely to have been a victim in ARH police incidents and 2 times more likely to have an undiagnosed alcohol-related hospital admission than men. Victims and offenders predominantly came from disadvantaged areas and major cities. Aboriginal individuals were overrepresented as both offenders and victims. A significant proportion of individuals experienced emergency department presentations or hospital admissions, with head injuries being the most common. Assault causing bodily harm was the most prevalent offence resulting in hospitalisation (66%, n = 2,018). Conclusions There is a noteworthy disparity between the quantity of hospital admissions attributed to alcohol-related incidents and the number of cases that are formally classified as ARH in the hospital system. This disparity highlights a more profound issue of substantial under-ascertainment or inadequate identification of ARH than previously acknowledged. Our findings justify the prioritisation of prevention strategies, beyond improvement in the documentation of alcohol-related hospitalisation. Considering the scale of the problem, and the underestimation of the burden of alcohol-related hospitalisation, a proportional increase in investment is necessary to achieve population-level reductions in ARH.